PENERAPAN MODEL MORAL REASONING BERBANTUAN MEDIA KARTU DILEMA UNTUK MENINGKATKAN SIKAP PEDULI LINGKUNGAN SISWA KELAS V PADA MATA PELAJARAN PENDIDIKAN PANCASILA - Nur Adma, Rindani; Syahrul Rizal, Muhammad; Aprinawati, Iis; Masrul; Ediputra, Kasman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of environmental care attitudes among fifth-grade students at SDM 027 Batubelah, as indicated by initial observation data across four indicators: cleaning trash bins (29.6%), cleaning the school environment (22.2%), maintaining the school garden (7.4%), and maintaining environmental cleanliness (44.4%). The objective of this study is to improve students' environmental care attitudes through the application of the Moral Reasoning model assisted by Dilemma Cards. This study is a Classroom Action Research (CAR) using the Kemmis & Taggart design, conducted in two cycles, each consisting of two sessions. The research subjects were 26 fifth-grade students at SDM 027 Batubelah. Data collection instruments included the "Aksi Nyata" (Real Action) observation sheet, teacher and student activity observation sheets, worksheets, and interview guidelines. The results showed consistent improvement in each session. Classical mastery increased from 36% (Cycle I, Session 1) to 52% (Cycle I, Session 2), then rose to 64% (Cycle II, Session 1) and reached 80% (Cycle II, Session 2), exceeding the minimum success indicator of 75%. The average class score also rose steadily from 45.60% in the pre-action stage to 86.28% by the end of Cycle II. Thus, the Moral Reasoning model assisted by Dilemma Card media proved effective in improving the environmental care attitudes of fifth-grade students in the Pancasila Education subject.